2016
DOI: 10.17153/oguiibf.272308
|View full text |Cite
|
Sign up to set email alerts
|

Ekonomik Büyüme ve Gelir Eşitsizliği İlişkisi: Kuznets Ters-U Hipotezi’nin Geçerliliği

Abstract: This study aims to determine effects of economic growth on income inequality by classifiying countries in terms of their level of development. The validity of Kuznets's inverted-U shaped hypothesis is tested for four different panels that is divided as low and low-middle income countries, upper-middle income countries, high income countries and all countries. This paper examines that the relationship between economic growth and income inequality by using data for the period of 1995-2011 and 94 countries. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
1
0
4
Order By: Relevance
“…According to Kuznets, in the early stages of economic growth, the inequality in income distribution increases, income inequality remains constant for a while at the highest point and decreases in the following period, thus the Kuznets curve takes the shape of an inverted U. Anand & Kanbur (1993), Barro (2000), Thornton (2001), Chen (2003), Topuz & Dağdemir (2016), Şengür (2020) achieved similar results with Kuznets. Ram (1991), Ram (1997), Acemoglu & Robinson (2002), Gallup (2012), Kiatrungwilaikun & Suriya (2015), Oczki et al (2017), Çakmak & Tosun (2017), Jovanovic (2018), Abdioğlu et al (2019), concluded that in contrast to Kuznets, there is a U-shaped relationship between income inequality and economic growth.…”
Section: Literaturementioning
confidence: 84%
See 1 more Smart Citation
“…According to Kuznets, in the early stages of economic growth, the inequality in income distribution increases, income inequality remains constant for a while at the highest point and decreases in the following period, thus the Kuznets curve takes the shape of an inverted U. Anand & Kanbur (1993), Barro (2000), Thornton (2001), Chen (2003), Topuz & Dağdemir (2016), Şengür (2020) achieved similar results with Kuznets. Ram (1991), Ram (1997), Acemoglu & Robinson (2002), Gallup (2012), Kiatrungwilaikun & Suriya (2015), Oczki et al (2017), Çakmak & Tosun (2017), Jovanovic (2018), Abdioğlu et al (2019), concluded that in contrast to Kuznets, there is a U-shaped relationship between income inequality and economic growth.…”
Section: Literaturementioning
confidence: 84%
“…Çalışmada gelir eşitsizliği ve ekonomik büyüme arasında U şeklinde ilişki olduğu bulgusu elde edilmiştir. Topuz & Dağdemir (2016), 1995-2011 2019), ekonomik büyüme ve gelir eşitsizliği arasındaki ilişkiyi incelerken, Kuznets ters U eğrisinin geçerliliğini Türkiye için zaman serisi analizi ile test etmişlerdir. Çalışma, 1978-2016 yıllarını kapsamakta olup, gelir eşitsizliği ölçüsü olarak Gini katsayısı ve ekonomik gelişme ölçüsü olarak kişi başına düşen milli gelir değişkenleri kullanılmıştır.…”
Section: Literatür Taramasıunclassified
“…Literatür incelendiğinde gelir eşitsizliği ve ekonomik büyüme arasında uzun vadede negatif ilişkinin var olduğunu ifade eden Kuznets Ters U hipotezini destekleyen çalışmaların giderek arttığını söylemek mümkündür (Persson ve Tabellini, 1991;Alesina ve Perotti, 1993;Clarke, 1995;Perotti, 1996;Dawson, 1997;Nielsen ve Alderson, 1997;Forbes, 2000;Easterly, 2001;Knowles, 2005;Barro, 2008;Özdemir vd., 2011;Peçe vd., 2016;Topuz ve Dağdemir, 2016;Akalin vd., 2018;Kamacı, 2019;Takım vd., 2020;Şengür, 2020;Göcen, 2021).…”
Section: Ekonomik Büyüme-gelir Dağılımı İlişkisiunclassified
“…(2022) az gelişmiş ülkelerde gelir eşitsizliğinin temelde kır-kent eşitsizliğinden kaynaklı olarak gerçekleştiğini ve kentleşmenin kır-kent ayrımını olumlu etkileyeceğini, iyi yönetilen kentleşmeyi teşvik ederek gelir eşitsizliğini azaltacağını öne sürmüşlerdir. Şehirleşmenin önemli sonuçlarından biri olan ekonomik büyüme ve gelir eşitsizliği ilişkisi, Topuz ve Dağdemir (2016) tarafından 94 ülke için, 1995-2011 verileri kullanılarak araştırılmıştır. Elde edilen bulgular, Kuznets'in (1955) ortaya koyduğu gelir artışına bağlı olarak meydana gelecek gelir eşitsizliğinin belirli bir eşik gelir düzeyine kadar artıp, belirli bir eşik gelir düzeyinden sonra azalacağına dair hipotezi desteklemektedir.…”
Section: şEhirleşme-gelir Eşitsizliği İlişkisiunclassified